Opinion on Student’s Educational Performance and Sleeping Patterns Using Data Analytics Technique - Jemima Jebaseeli, T.; Venkatesan, R.; M., Selvarathi; Jasmine David, D. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Sleep deprivation habits are widespread in students and may render them prone to mental illnesses, drug misuse, and decreased educational attainment. Sleep problems including insomnia, parasomnia was notably high among engineering students due to their rigorous academic schedules, exposure to social media, and gaming activity. Sleep postponement of bad sleepers is larger compared to that of healthy sleepers. Sufficient sleep has a significant function in boosting cognitive skills primarily retention of information. Inadequate late night sleep quality and the subsequent midday drowsiness impair the cognitive and behavioral health of students’ academic performance. This study aims to examine the link between sleep disorders and educational results for graduates of engineering. Every candidate must be drug-free and non-medicated is considered for this research. We exclude individuals who tend to abuse prescription medicines for non-medical purposes. Using a self-reported assessment, sleeping disorder’s impact on student achievement is assessed. After adequate validation, academic performance data was obtained from the participants. The proposed system is deriving the connection between the variables is using statistical approaches.